ASEAN’s Humanitarian Conscience: SEAHUM’s Collective Support for Gaza through English School Lens - Firdaus Guritno (Indonesian Red Crescent Humanitarian Journal, 2026)
This paper analyzes the Southeast Asia Humanitarian Committee, known as SEAHUM, through the English School theory in International Relations. The research shows how humanitarian cooperation in the region helps the development of global moral order. SEAHUM as an Organization Alliance that was established in 2012, brings together 24 humanitarian groups and 9 observers from ASEAN nations brings a network that coordinates disaster response, advocacy, and transnational humanitarian assistance in the region. This paper examines how non-state regional actors like SEAHUM as a case study can embody solidarist principles by their humanitarian response to Gaza within an evolving regional international society. The English School framework used to highlight SEAHUM’s role in expanding humanitarian responsibility beyond the pluralist norms of sovereignty and non-interference that traditionally define ASEAN as a region. Based on SEAHUM official data between 2023 and 2025, member organizations collectively distributed more than IDR 165 billion or approximately 10 million USD in assistance to Gaza. Humanitarian assistance organized by SEAHUM members including food, medical services, shelter, and water. These coordinated efforts illustrate how regional solidarism formed by SEAHUM can materialize through organized humanitarian action to link moral concern among the region with practical cooperation. This study contributes to the existing English School literature by demonstrating that solidarism is not limited to interstate relations only but can also be institutionalized through regional civil society networks. This study also expands theoretical understanding of international society by revealing how SEAHUM as a Southeast Asia’s humanitarian community can operate as a moral actor in global politics.